Surrounding Rock Deformation Mechanism and Control Technology for Gob-Side Entry Retaining with Fully Mechanized Gangue Backfilling Mining: A Case Study - Peng Gong; Zhanguo Ma; Ray Ruichong Zhang; Xiaoyan Ni; Fei Liu; Zhimin Huang (Shock and Vibration)
To counter the technical difficulties faced by gob-side entry retaining (GER) under multiple complex mining geological conditions in China, this paper introduces a GER method with fully mechanized gangue backfilling mining. A similar materials simulation experiment was conducted to simulate the gob-backfilled GER process by using the similar model test system containing an independently developed horizontal pushing load device. The experimental results show that the compaction speed of the backfilling area (BFA) can be improved, and the main roof subsidence can be reduced by increasing the horizontal pushing load and reducing the attenuation rate of the stress in BFA. The designed roadside backfill body (RBB) containing a flexible cushion is adaptive to the given deformation of the main roof, thus reducing the stress concentration of the RBB. The field test results show that when a 2 MPa horizontal pushing load is exerted in the BFA, arranging a 200 mm high-water-material flexible cushion can cause the BFA to swiftly change to the compaction stage. After stabilized deformation, the roadway section satisfies the design and application requirements. The feasibility and rationality of the GER with the fully mechanized gangue backfilling mining are proved, providing a safe, efficient, and environmentally friendly mining method without using a coal pillar.